Role of omentin and vaspin in metabolic diseases in association with psoriasis - Kiluk, Paulina; Baran, Anna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2017)
Psoriasis is a chronic skin disease characterized by systemic inflammation associated with an increased risk of metabolic and cardiovascular complications. A special role in maintaining systemic inflammation is attributed to obesity. Adipose tissue is an active endocrine organ which, through adipokine secretion, is involved in the regulation of many systemic metabolic pathways. Obesity increases the risk of developing type 2 diabetes mellitus, atherosclerosis, cardiovascular diseases and hypertension. The paper presents the characteristics of two relatively recently discovered and little known adipokines: omentin and vaspin. They are considered to have beneficial effects preventing the development of metabolic disorders associated with obesity. In addition, attention was given to their possible involvement in the pathogenesis of psoriasis and potential use as markers of disease severity and the risk of developing metabolic complications.